The Enigma of the Dichotomic Pressure Response of GluN1-4a/b Splice Variants of NMDA Receptor: Experimental and Statistical Analyses - Bliznyuk, Alice; Gradwohl, Gideon; Hollmann, Michael; Grossman, Yoram (Frontiers in Molecular Neuroscience, 2016)
Professional deep-water divers, exposed to hyperbaric pressure (HP) above 1.1 MPa, develop High Pressure Neurological Syndrome (HPNS), which is associated with CNS hyperexcitability. It was previously reported that HP augments N-methyl-D-aspartate receptor (NMDAR) synaptic response, increases neuronal excitability and potentially causes irreversible neuronal damage. Our laboratory has reported differential current responses under HP conditions in NMDAR subtypes that contain either GluN1-1a or GluN1-1b splice variants co-expressed in Xenopus laevis oocytes with all four GluN2 subunits. Recently, we reported that the increase in ionic currents measured under HP conditions is also dependent on which of the eight splice variants of GluN1 is co-expressed with the GluN2 subunit. We now report that the NMDAR subtype that contains GluN1-4a/b splice variants exhibited 'dichotomic' (either increased or decreased) responses at HP. The distribution of the results is not Normal thus ANOVA test and clustering analysis were employed for statistical verification of the grouping. Furthermore, the calculated constants of alpha function distribution analysis for the two groups were similar, suggesting that the mechanism underlying the switch between an increase or a decrease of the current at HP is a single process, the nature of which is still unknown. This dichotomic response of the GluN1-4a/b splice variant may be used as a model for studying reduced response in NMDAR at HP. Successful reversal of other NMDAR subtypes response (i.e. current reduction) may allow the elimination of the reversible malfunctioning short term effects (HPNS), or even deleterious long term effects induced by increased NMDAR function during HP exposure.